2005
DOI: 10.1128/jcm.43.7.3244-3246.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Recovery of Microorganisms from BacT/ALERT Plastic and Glass FA and FN Blood Culture Bottles

Abstract: bioMerieux, Inc., has recently introduced plastic bottles to replace glass bottles for use in the BacT/ALERT blood culture system. We compared the performance of the plastic to the glass bottles in a large clinical evaluation. Two blood cultures were collected from each patient, one using glass FA (aerobic) and FN (anaerobic) bottles and one using plastic FA and FN bottles. Of the 4,040 sets of four bottles collected, 3,110 contained the recommended 8 to 12 ml of blood, yielding 524 microorganisms with 359 jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Similar observation was seen in a study from a super specialty hospital in New Delhi where paired blood cultures were 13.70% positive and single blood culture was 4.59% positive [15]. The use of 2 aerobic blood cultures has also been controversial as many studies have recommended the pairing of anaerobic blood culture with aerobic blood culture and many others have contradicted the use of anaerobic-aerobic blood culture [16][17][18][19][20]. However the result of our study supports the use of two aerobic blood cultures.…”
Section: Discussionsupporting
confidence: 69%
“…Similar observation was seen in a study from a super specialty hospital in New Delhi where paired blood cultures were 13.70% positive and single blood culture was 4.59% positive [15]. The use of 2 aerobic blood cultures has also been controversial as many studies have recommended the pairing of anaerobic blood culture with aerobic blood culture and many others have contradicted the use of anaerobic-aerobic blood culture [16][17][18][19][20]. However the result of our study supports the use of two aerobic blood cultures.…”
Section: Discussionsupporting
confidence: 69%
“…There are several commercial culture vials used by BD BACTEC FX40 and BacT/Alert systems, with no apparent effects on recovery results [31], but with a wide window of standardization opportunities. Nevertheless, as these systems have been developed to assess the microbial contamination of blood samples, their manufacturers do not have to comply with GMP validations guidelines and thus are unaware of resulting implications on their user validations for improvement of ATMPs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the recovery rates of some microorganisms, especially Pseudomonas spp. and fungi, are significantly lower in anaerobic media than in aerobic media (4,(8)(9)(10)(11)(12)17). Interestingly, in the work of Lee et al (5), both P. aeruginosa and C. albicans showed the lowest detection rates if only one or two blood cultures were considered.…”
Section: Assessing How Many Blood Cultures Are Needed For Detecting Bmentioning
confidence: 99%